Linguistic Features of Artistic Similes - Botyrova Makhliyo; Bozorova Gulshan Chorshanbi kizi (Central Asian Journal of Literature, Philosophy and Culture, 2022)
The article discusses the linguistic analysis of artistic similes that are important in the text of a work of art. The scientific views of several scientists about similes are discussed. In linguistics, various opinions are given and explained about common and artistic similes and their peculiarities. On the example of Odil Yaqubov's work “Oqqushlar, oppoq qushlar…”, we draw similes into linguistic analysis.